Bringing Child-Friendly Village into Reality through Community Empowerment in Indonesia - Agustinawati, Eva Agustinawati (Advances in Social Sciences Research Journal, 2018)
The problem befalling child appears more frequently in many social media with a very variety of complex causes and effects. Government issued child-friendly city policy in some regions called child-friendly village. Public participation is needed for implementing program through community empowerment. This research aimed to find out how child-friendly city can be brought into reality through community empowerment in Indonesia. This research employed Grounded Theory approach with purposive sampling and snowball sampling being the sampling techniques. Data analysis was conducted using domain analysis, taxonomic analysis, componential analysis, and discovering cultural themes. The result of research showed that child-friendly village program was initiated by people from idea, planning, implementing to monitoring and evaluating. This program was helped by PT. Sari Husada through CSR (Corporate Social Responsibility) and successfully brought child-friendly village into reality. Keywords: child, empowerment, community